Changes in Children’s Height in Japan and South Korea in the Past Half Century: The Roles of Fruit/Vegetables on Top of Animal Protein - Mori, Hiroshi (European Journal of Applied Sciences, 2021)
Children in Japan and South Korea in North East Asia grew in height unprecedentedly fast,1 cm per decade in the post war economic prosperity. Food consumption increased in quantity and quality as well, with caloric supply from animal products augmented. Children in Japan began to grow much slower in the1980s and ceased to grow at all ages in the early 1990s, while animal protein supply was still on the rise. Children in Korea kept growing taller in the 1990s and overtook their Japanese peers by 3.0 cm in mean height in the mid-2000s, even though per capita consumption of animal products was still lower than in Japan. Children in Korea then suddenly ceased to grow taller in mean height, while per capita supply of animal products kept increasing vigorously toward the end of the 2010s. It was discovered that children started to turn away from vegetables in their diets in the beginning of the 1990s and strikingly, ate less than 10% of the volume eaten by the older generation in their 50s-60s in the end of the 2010s. As the author has repeatedly emphasized, children in Japan started to reduce consumption of fruit a decade before they stopped growing taller in the early-1990s. Fruit and/or vegetables seem to have something to do with the human metabolism, which calls for in-depth biological researches.